The Role of AI in Enhancing the Academic Achievement of Slow Learners in the Batticaloa District - Abilash.K; Mahthi Hassan.N (Penerbit Hellow Pustaka, 2025)
This study investigates the impact of AI powered learning systems on improving the academic achievement of slow learners within the 21st century educational landscape of inclusive education. The research seeks to determine how AI technologies can help identify specific student challenges, reduce learning gaps, and provide customized learning experiences. The ultimate goal is to build self-confidence, increase student engagement, and improve overall learning efficiency in the classroom. A main challenge identified in the study is the digital divide-the lack of technical facilities and internet access for students in rural and underdeveloped areas. To address this, a mixed-methods approach was used, involving 200students, 250teachers, 10 in-service advisors(ADS/ISAs), and 80parents from all five zones in the Batticaloa District. Data on performance were collected through questionnaires, interviews, observations, and document analysis, with subsequent analysis performed using SPSS software. Findings indicate that AI-based interventions can significantly improve student achievement by creating customized learning paths and adapting the curriculum to individual learning speeds. AI’s impact has fundamentally changed the roles of teachers, the tools they use, and the content they deliver. The research also revealed that AI tools can empower teachers to provide immediate and necessary assistance. The study recommends creating localized, interactive AI learning resources, offering comprehensive professional training for teachers, improving the distribution of technical facilities and fostering collaboration with policymakers. By implementing these recommendations, the country can better achieve its future educational goals and adapt to timely technological changes. This study also emphasizes the important of conducting research not only on future technological developments but also on the rapid change occurring in technology today.